STREET ART SEBAGAI KOMUNIKASI POLITIK OLEH PELAKU SENI JALANAN “SLINAT” DI DENPASAR (Jurnal Nawala Politika, 2023)
This study was made to answer about how the meaning and message of Slinat's mural acts as a political communication. In Slinat mural works, synonymous with the form of protest or criticism with the message and meaning in it. In answering these research questions, researchers will use Roland Barthes ' semiotics theory supported by the concept framework, namely; street art and political communication. This type of research is qualitative with Roland Barthes semiotic analysis research method. From the findings of the data and analysis that researchers have done, it was found that the message and meaning contained in each mural Slinat many refer to protest and criticism. Dominated by murals about the state of Bali, especially in Bali Tourism. Slinat took the streets as an alternative media, and every new artwork on the streets for him was an information and street art became an alternative communication media connecting people's aspirations Keyword: Street Art, Political Communication, Slinat, Semiotics